Ultrahigh-weather-resistance OC protection thermal transfer ribbon and preparation method thereof

By using a combination of multi-layer structure and specific resin additives on the thermal transfer carbon belt, the problem of insufficient performance of the carbon belt in high-speed printing is solved, and the effects of high weather resistance, high alcohol resistance and high gloss are achieved, which improves the carbon belt Adaptability and scope of use.

CN119283518AActive Publication Date: 2025-01-10HUNAN DINGYIYUAN TECH DEV CO LTD +1

Patent Information

Application Number
CN202411298681.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-10
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

It is difficult for existing thermal transfer carbon tapes to take into account high weather resistance, high alcohol resistance and high gloss properties under high-speed printing conditions, and the foil retention performance of the single-layer carbon tape is insufficient, which affects the quality of the finished product.

Method used

The OC protection carbon tape with a multi-layer structure, including a back coating, a release layer, a cured layer and a subsequent layer, optimizes the performance of the carbon tape to improve foil retention, weathering and gloss through the combination of specific resins and additives.

Benefits of technology

Under high-speed printing conditions, OC protection carbon tape achieves good foil retention, while taking into account high weather resistance, high alcohol resistance and high gloss properties, improving the use range and adaptability of thermal transfer carbon tape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119283518A_ABST
    Figure CN119283518A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrahigh-weather-resistance OC protection thermal transfer ribbon and a preparation method thereof, and relates to the technical field of thermal transfer printing. The OC protection thermal transfer ribbon comprises a bonding layer, a curing layer, a stripping layer, a base material and a back coating layer which are sequentially arranged from top to bottom. The stripping layer is prepared from the following raw materials in parts by weight: 19 to 22 parts of second resin, 0.5 to 0.7 part of a release agent, 1.8 to 2.2 parts of a solid lubricant, 0.9 to 1.2 parts of a dispersing agent, 26 to 32 parts of a light stabilizer, 0.3 to 0.6 part of an antioxidant and 0.5 to 0.8 part of an antistatic agent; the curing layer comprises the following raw materials in parts by weight: 18-22 parts of third resin, 2-4 parts of an isocyanate curing agent and 19-22 parts of a reactive light stabilizer; the bonding layer is prepared from the following raw materials in parts by weight: 8 to 12 parts of fourth resin, 2 to 4 parts of an auxiliary agent and 0.8 to 1.1 parts of a dispersing agent. The OC protection thermal transfer ribbon obtained by the invention has good foil retentivity in high-speed printing, and also has high weather resistance, high alcohol resistance and high glossiness at the same time. The thermal transfer ribbon can be applied to different scenes, and the application range and adaptability of the thermal transfer ribbon are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal transfer printing, and in particular to an ultra-high weather-resistant OC protective carbon belt and a preparation method thereof. Background Art

[0002] In view of the special demand of high weather resistance, high alcohol resistance, high gloss and foil retention performance of carbon ribbons under high-speed printing of soft labels, there are many problems with the protective films currently on the market: First, thermal sublimation ribbons use small molecule dyes, which absorb light energy, increase their energy levels, and are in an excited state. The color development system of the dye molecules changes or is destroyed, causing the dye to decompose and discolor or fade. Therefore, a high weather resistance protective layer needs to be set on the pattern surface, but most carbon ribbons on the market have poor weather resistance and alcohol friction resistance due to the migration of resins and additives, and cannot take both into account at the same time; second, under high-speed printing conditions, the heating and pressurization method of the print head causes the foil retention performance of the single-layer carbon ribbon to be insufficient, affecting the continuous printing and quality of the finished product; third, under high-speed printing conditions, the heating and pressurization method of the print head requires the carbon ribbon protective layer to have good demolding performance, otherwise it will affect the glossiness of the surface of the thermal sublimation pattern.

[0003] Therefore, it is urgently needed to provide a thermal transfer carbon ribbon that has high weather resistance, high alcohol resistance, high gloss and foil retention performance under high-speed printing of soft labels. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an ultra-high weather resistance OC protective carbon tape and a preparation method thereof. The OC protective carbon tape prepared by the present invention has a back coating layer on one side of the substrate and an OC protective layer (including a peeling layer, a curing layer and an adhesive layer) on the other side. The OC protective carbon tape obtained by the present invention can have good foil retention in high-speed printing, and can also take into account high weather resistance, high alcohol resistance and high gloss performance. It can be applied to different scenarios, which improves the scope of use and adaptability of thermal transfer carbon tapes.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] The first object of the present invention is to provide an ultra-high weather-resistant OC protective carbon tape, comprising an adhesive layer, a curing layer, a peeling layer, a substrate, and a back coating layer arranged in sequence from top to bottom;

[0007] The release layer comprises the following raw materials in parts by weight: 19-22 parts of a second resin, 0.5-0.7 parts of a release agent, 1.8-2.2 parts of a solid lubricant, 0.9-1.2 parts of a dispersant, 26-32 parts of a light stabilizer, 0.3-0.6 parts of an antioxidant, and 0.5-0.8 parts of an antistatic agent;

[0008] The curing layer comprises the following raw materials in parts by weight: 18-22 parts of a third resin, 2-4 parts of an isocyanate curing agent, and 19-22 parts of a reactive light stabilizer;

[0009] The adhesive layer comprises the following raw materials in parts by weight: 8-12 parts of a fourth resin, 2-4 parts of an auxiliary agent, and 0.8-1.1 parts of a dispersant.

[0010] The beneficial effects of the present invention are as follows: the protective carbon tape of the present invention comprises a substrate, one side of the substrate is provided with a back coating layer, and the other side is provided with an OC protective layer (including a peeling layer, a curing layer and an adhesive layer). The present invention adjusts the composition structure of the carbon tape, and by setting a multi-layer structure and different combinations of various additives, not only can the various properties be taken into account at the same time, but also can be applied to different scenes, thereby improving the scope of use and adaptability of the carbon tape. The protective carbon tape obtained by the present invention has good foil retention in high-speed printing, and can also take into account high weather resistance, high alcohol resistance and high gloss performance at the same time, and can be well used in high-speed printing of soft labels.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Further, the back coating layer comprises the following raw materials in parts by weight: 9-11 parts of a first resin, 2-4 parts of an isocyanate curing agent, 0.5-1 parts of an inorganic filler, 0.5-0.9 parts of a release agent, and 0.3-0.5 parts of an organic silicone oil;

[0013] The first resin is a thermoplastic resin;

[0014] The isocyanate curing agent includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and aromatic isocyanate;

[0015] The inorganic filler includes at least one of talc, kaolin, calcium carbonate, aluminum hydroxide, silicon dioxide, graphite, and boron nitride;

[0016] The release agent in the back coating layer includes at least one of phosphate ester, metal soap, silicone oil, and surfactant.

[0017] The beneficial effects of adopting the above further scheme are: the role of the back coating is to provide smoothness at different printing temperatures, avoid adverse effects such as lateral wrinkles or stickiness during printing, and clean and protect the print head and ensure uniform heat transfer, so that the glossiness of the front layer after transfer is improved, the surface roughness is reduced, and the wear resistance of the protective layer is improved. In order to improve the heat resistance of the back coating during printing, improve the adhesion between the back coating and PET, and reduce the viscosity at high temperatures, an isocyanate curing agent can be added to the above resin, and an inorganic filler and a release agent need to be added to the back coating to maintain the excellent smoothness of the carbon ribbon during high-speed printing.

[0018] Preferably, the first resin includes at least one of polyester resin, polyacrylate resin, polyvinyl acetate resin, styrene acrylate resin, polyurethane resin, polyethylene resin, polypropylene resin, polystyrene resin, polyvinyl chloride resin, polyether resin, polyamide resin, polyimide resin, polyamideimide resin, polycarbonate resin, polyacrylamide resin, polyvinyl chloride resin, polyvinyl butyral resin, polyvinyl acetal resin, and polyvinyl acetal resin;

[0019] Preferably, the first resin further comprises a silicone modified product of the above resin.

[0020] Preferably, the first resin is polyvinyl butyral resin.

[0021] Preferably, the aromatic isocyanate includes, but is not limited to, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, toluidine diisocyanate, and p-phenylene diisocyanate.

[0022] Preferably, the inorganic filler is talcum powder with a mesh size of 5000-11000.

[0023] Preferably, the release agent is a phosphate ester.

[0024] Preferably, the inorganic filler has a D50 particle size of 1.0-5 um and a D90 particle size of 3-10 um.

[0025] The beneficial effect of adopting the above scheme is: in order to ensure that the inorganic filler is evenly dispersed in the resin, improve the good thermal conductivity of the back coating, improve the gloss after transfer, reduce the surface roughness, and improve the wear resistance, it is necessary to control the overall particle size and particle size distribution of the back coating filler. If the requirements cannot be met, grinding treatment is required.

[0026] Further, the second resin includes at least one of acrylonitrile-butadiene-styrene copolymer resin, polystyrene resin, polycarbonate resin, polymethyl methacrylate resin, and polyacrylic acid resin;

[0027] The release agent in the release layer is at least one of a solid release agent and a liquid release agent;

[0028] The solid lubricant includes at least one of talcum powder, wax powder and metal soap;

[0029] The dispersant in the peeling layer includes at least one of a cationic wetting dispersant, an anionic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, and a polymeric super dispersant;

[0030] The light stabilizer in the release layer includes at least one of a light shielding agent, an ultraviolet absorber, a quencher, a free radical scavenger, and a hydroperoxide decomposer;

[0031] The antioxidant includes at least one of a hindered phenol antioxidant, a phosphite antioxidant, a thio antioxidant, a composite antioxidant, and a hindered amine antioxidant;

[0032] The antistatic agent includes at least one of sulfuric acid derivatives, phosphoric acid derivatives, amines, quaternary ammonium salts, imidazoles, and ethylene oxide derivatives.

[0033] The beneficial effects of adopting the above further scheme are: the role of the peeling layer in the present invention is to ensure that the peeling layer can be demolded smoothly during printing; second, to provide glossiness on the pattern surface after printing is completed; third, to provide UV protection in indoor environments and extend the storage life of the finished product; fourth, to provide a certain degree of alcohol friction resistance protection.

[0034] The peeling layer uses a resin with high gloss to ensure that the peeling layer has good gloss on the pattern surface after printing. In order to further improve the gloss of the peeling layer, a certain amount of release agent needs to be added to the peeling layer. In addition, a solid lubricant needs to be added to improve the wear resistance of the peeling layer. In order to reduce the time and energy required to complete the dispersion process during powder grinding, a certain amount of dispersant needs to be added. A certain amount of light stabilizer needs to be added to the coating to improve the indoor weather resistance of the product. In addition, in order to extend the service life of the product, a certain amount of antioxidant needs to be added to the coating. In order to promptly eliminate the static electricity accumulation generated by the carbon ribbon during the printing process due to friction, and to prevent adverse conditions such as static electricity adsorption, dust absorption, and fire discharge, a certain amount of antistatic agent can be added to the peeling layer.

[0035] Preferably, considering the release effect and weather resistance of the peeling layer, the second resin is preferably a thermoplastic acrylic resin, and more preferably a resin with a Tg of 80-130° C. and a molecular weight of 30,000-200,000.

[0036] Preferably, the talcum powder has a mesh size of 5000-12000 and a specific surface area of ​​5-10 g / m 2.

[0037] Preferably, the light stabilizer is a solid triazine ultraviolet absorber.

[0038] Preferably, the light stabilizer is a solid triazine ultraviolet absorber with a melting point of 85-110° C. and a molecular weight of 300-700.

[0039] The beneficial effect of adopting the above scheme is that the absorption mechanism of triazine ultraviolet absorbers is based on two parts. One is that the compound is a conjugated π electron system structure, and the other is that the structure of the compound can move hydrogen. Among them, the ortho-hydroxyl group on the benzene ring and the nitrogen atom on the adjacent triazine ring can form an intramolecular hydrogen bond to form a six-membered ring, and the six-membered ring and the surrounding structure form a conjugated system. The energy range required to open the chelate ring is just close to the ultraviolet light energy within the UVA and UVB range. When the molecule itself absorbs ultraviolet light, the molecular energy increases, the weakest NH bond in the six-membered ring breaks, and the absorbed energy is released in the form of heat energy, fluorescence or phosphorescence that is harmless to the polymer material, and the molecular structure is restored, thereby repeatedly absorbing a large amount of ultraviolet light, which plays a role in protecting the polymer.

[0040] In addition, the UV resistance of solid UV absorbers is better than that of liquid ones. The reason is that the solid state can be better embedded in the coating resin, just like the effect of filler, so it is more resistant to migration and can show better resistance, while most liquid UV absorbers do not have this effect and are more likely to migrate during use, resulting in poor resistance; secondly, the alcohol friction resistance of solid UV absorbers is better than that of liquid ones. The solid state can be better embedded in the coating resin to maintain the tightness of the coating, while the liquid state will make the coating structure looser. At the same time, most liquid additives have good viscosity, and polyacrylic acid resins themselves are brittle, which will cause acrylic acid to form resin clumps due to the viscosity of the liquid additives during the friction process. The resin clumps will further damage the coating during the friction process, resulting in reduced alcohol resistance.

[0041] Preferably, the light stabilizer is a benzoate ultraviolet absorber. Since the main action range of the solid triazine ultraviolet absorber is UVA and UVB, in order to further improve the weather resistance, it is necessary to add an absorber that acts in the UVC band to be used in combination with it. The benzoate ultraviolet absorber can convert ultraviolet radiation into heat energy through reversible chemical rearrangement. The solid benzoate ultraviolet absorber preferably has a melting point of 190-250°C.

[0042] Further, the third resin includes at least one of polyester resin, polyacrylate resin, styrene acrylate resin, polyurethane resin, polyethylene resin, polypropylene resin, polyolefin resin, polystyrene resin, polyvinyl chloride resin, polyvinyl butyral resin, amino resin, epoxy resin, hydroxyl-modified acrylic resin, hydroxyl-modified vinyl chloride-acrylate resin, polyester-modified acrylic resin, and acrylic-modified polyester resin;

[0043] The isocyanate curing agent in the curing layer includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and aromatic isocyanate;

[0044] The reactive light stabilizer includes at least one of a phenol compound ultraviolet absorber, a benzotriazole ultraviolet absorber, a benzophenone ultraviolet absorber, an oxalamide ultraviolet absorber, and a triazine ultraviolet absorber.

[0045] The beneficial effects of adopting the above further scheme are: the functions of the curing layer in the present invention are firstly to increase the adhesion of the coating and isolate the influence of water and air on the oxidation and fading of the dye; secondly, to reduce the migration rate of the ultraviolet absorber and improve the weather resistance; in order to increase the adhesion of the coating, the curing layer component is suitably selected from thermoplastic resins containing reactive groups. In order to improve the adhesion of the curing layer, isocyanate compounds can be added to the above thermoplastic resins. In order to improve the weather resistance and prevent the migration of the ultraviolet absorber, a certain amount of reactive light stabilizer needs to be added to the coating. The ultraviolet absorber can be fixed in the coating by reacting with the curing agent, reducing the migration of the ultraviolet absorber, thereby improving its weather resistance.

[0046] Preferably, the third resin is at least one of hydroxyl-modified acrylic resin, polyhydroxyl-modified vinyl chloride-acrylate resin, polyester-modified acrylic resin, acrylic-modified polyester and the like.

[0047] Preferably, in view of interlayer adhesion and weather resistance, the third resin is a polyhydroxy-modified vinyl chloride-acrylate resin having a Tg of 60-75° C. and a molecular weight of 10,000-50,000.

[0048] Preferably, the isocyanate curing agent is an aromatic isocyanate, including but not limited to 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, toluidine diisocyanate, and p-phenylene diisocyanate.

[0049] Further, the fourth resin includes at least one of cellulose-based resin, polyvinyl acetate resin, polyvinyl alcohol resin, polyurethane resin, polyamide resin, polyester resin, polyacrylic resin, polyolefin resin, polystyrene resin, styrene acrylate resin, vinyl chloride-acrylate resin, vinyl chloride-vinyl acetate resin, and vinyl chloride-vinyl isobutyl ether resin;

[0050] The auxiliary agent includes at least one of inorganic particles and solid lubricants;

[0051] The dispersant in the adhesive layer includes at least one of a cationic wetting dispersant, an anionic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, and a polymeric super dispersant.

[0052] The beneficial effects of adopting the above further scheme are: the functions of the bonding layer in the present invention are the following three points: first, after printing is completed, the bonding layer is located on the pattern receiving layer to provide adhesion between the coatings; second, it provides the main alcohol friction resistance; third, it provides foil retention of the carbon ribbon to prevent the coating resin from falling off during use.

[0053] The adhesive layer is preferably composed of thermoplastic resin as the base. To further enhance the friction resistance of the adhesive layer, a certain amount of additives needs to be added to the coating. In addition, to reduce the time and energy required to complete the dispersion process during powder grinding and stabilize the dispersion after grinding, a certain amount of dispersant needs to be added.

[0054] Preferably, in view of the alcohol resistance, film-forming property and compatibility with the pattern receiving layer of the resin, the fourth resin is at least one of polyurethane resin, polyacrylic resin and polyvinyl chloride resin.

[0055] Preferably, the fourth resin is a vinyl chloride-vinyl acetate resin having a Tg of 60-80° C., a vinyl acetate content of 10-20%, and a molecular weight of 30,000-100,000.

[0056] Preferably, the dispersant is a polymer type hyperdispersant.

[0057] Further, the solid release agent includes at least one of polyethylene wax, palmitamide, ethylene bislauric acid amide, behenic acid amide, ethylene bisoleic acid amide, stearic acid amide, ethylene bisstearic acid amide, oleic acid amide, erucic acid amide, oleyl palmitamide, octadecyl stearic acid amide, octadecyl erucic acid amide, pentaerythritol tetrastearate, glyceryl trihydroxystearate, zinc stearate, zinc stearyl phosphate, calcium stearate, magnesium stearate, talc, and wax powder;

[0058] The liquid release agent includes at least one of silicone oil, liquid paraffin, chlorinated paraffin, and n-butyl stearate.

[0059] Preferably, the release agent is a solid release agent.

[0060] Preferably, the melting point of the solid release agent is 50°C-120°C.

[0061] Preferably, the solid lubricant is talcum powder, the mesh size of the talcum powder is 5000-12000, and the specific surface area is 5-10g / m 2 .

[0062] Furthermore, the inorganic particles include at least one of silicon dioxide, aluminum oxide, titanium dioxide, molybdenum disulfide, calcium carbonate, and talc; when the auxiliary agent is the solid lubricant, the solid lubricant includes at least one of microcrystalline wax, carnauba wax, paraffin, low molecular weight polyethylene wax, wood wax, honey wax, spermaceti, wool wax, candelilla wax, vaseline, polyester wax, modified wax, and metal soap compounds.

[0063] The beneficial effect of adopting the above further solution is: in order to further improve the friction resistance of the bonding layer, a certain amount of additives needs to be added to the coating.

[0064] Preferably, the inorganic particles have a mesh size of 5000-12000 and a specific surface area of ​​5-10 g / m 2 of fine talcum powder.

[0065] Preferably, the molecular weight of the low molecular weight polyethylene wax is 2000-5000.

[0066] Preferably, the metal soap compound is at least one of zinc stearate, zinc stearyl phosphate, calcium stearate and magnesium stearate.

[0067] Furthermore, the substrate is a transparent flexible plastic film, including at least one of polypropylene, polyethylene naphthalate, polyethylene terephthalate, polyethylene, polyvinyl alcohol, and polymethyl methacrylate.

[0068] Preferably, the surface roughness Ra of the substrate is 0.02-0.1 nm.

[0069] The beneficial effect of adopting the above scheme is that the surface roughness of the substrate affects the glossiness of the coating after transfer, and the lower the surface roughness, the higher the glossiness.

[0070] Furthermore, the thickness of the substrate is 4 μm-50 μm, and the surface roughness Ra is 0.02-0.1 nm; the thickness of the back coating is 0.4 μm-1.2 μm; the thickness of the peeling layer is 0.3-5 μm; the thickness of the curing layer is 0.3-5 μm; and the thickness of the bonding layer is 0.1-1 μm.

[0071] The second object of the present invention is to provide a method for preparing an ultra-high weather-resistant OC protective carbon tape, which is as follows:

[0072] S1: Prepared liquid: Back coating liquid: Dissolve the first resin in a solvent, then add isocyanate curing agent, inorganic filler, and release agent to mix and dissolve to prepare back coating liquid for standby use; Stripping liquid: Dissolve the second resin in a solvent, then add release agent, solid lubricant, dispersant, light stabilizer, antioxidant, and antistatic agent to mix and dissolve to prepare stripping liquid for standby use; Curing liquid: Dissolve the third resin in a solvent, then add isocyanate curing agent and reactive light stabilizer to mix and dissolve to prepare curing liquid for standby use; Adhesive liquid: Dissolve the fourth resin in a solvent, then add auxiliary agent and dispersant to mix and dissolve to prepare adhesive liquid for standby use;

[0073] S2: applying corona to one side of the substrate;

[0074] S3: Coating: Apply the back coating liquid on the corona-charged surface of the substrate, and then dry it to form a back coating layer for standby use; then apply the stripping liquid on the side of the substrate away from the back coating layer, and then dry it to form a stripping layer; then apply the curing liquid on the side of the stripping layer away from the substrate, and then dry it to form a curing layer; apply the bonding liquid on the side of the curing layer away from the substrate, and then dry it to form a bonding layer, thereby obtaining an OC protective carbon tape.

[0075] Furthermore, the drying temperature of the back coating layer is 60-120°C, and the drying time is 0.5-2h; the drying temperature of the peeling layer is 60-120°C, and the drying time is 0.5-2h; the drying temperature of the curing layer is 60-120°C, and the drying time is 0.5-2h; the drying temperature of the bonding layer is 60-120°C, and the drying time is 0.5-2h. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 Schematic diagram of the structure of the OC protective carbon tape prepared in Examples 1-5 of the present invention.

[0077] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0078] 1- back coating layer, 2- substrate, 3- release layer, 4- curing layer, 5- adhesive layer. DETAILED DESCRIPTION

[0079] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0080] Example 1: Preparation of OC protective carbon tape

[0081] S1: Preparation: Back coating liquid: Dissolve 10 parts of polyvinyl butyral resin (S-LEC BH-6, Sekisui Chemical, Japan) in 60 parts of 2-butanone and 30 parts of toluene, then add 3 parts of isocyanate curing agent (TMHG-80B, Asahi Chemical, Japan), 0.6 parts of talcum powder (HY-TA05 with a particle size of 1.5um and a D90 particle size of 4.2um) D50; Haiyang Powder), 0.6 parts of phosphate ester (MOA-3PK-70; Jiangsu Haian Petrochemical Plant), 0.5 parts of silicone oil (KF-965-100cs; Shin-Etsu Silicone) were mixed and dissolved to prepare a back coating solution for use; stripping solution: 20 parts of thermoplastic acrylic resin (BR-52; Mitsubishi) were dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of solid release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc (MICROACE P-3; Japanese Talc), 1 part of dispersant (BYK180; Bi Ke), 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Heda) were mixed and dissolved to prepare a stripping solution for use; curing solution: 20 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) were dissolved in 38.2 parts of 2-butanone and 38.2 parts of toluene, and then 3 parts of isocyanate curing agent (TFD-90SB; Dornaide), 10 parts of ultraviolet absorber (Tinuvin400; liquid; BASF), and 10 parts of ultraviolet absorber (Tinuvin 1130; liquid; BASF) were added and mixed and dissolved to prepare a curing solution for use; bonding solution: 10 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) were dissolved in 43 parts of 2-butanone and 43 parts of toluene, and then 3 parts of talc powder (MICROACEP-3; Japan Talc) and 1 part of dispersant (LD-1010; Lida) were added and mixed and dissolved to prepare a bonding solution for use;

[0082] S2: A 4.5 μm PET film (Lumirror; Toray, Japan) with a surface roughness Ra of 0.04 nm was used as the substrate 2, and one side of the substrate 2 was corona-charged;

[0083] S3: Coating: Coating is performed by a gravure coater, firstly coating the back coating liquid on the corona-charged surface of the substrate 2 with a coating thickness of 0.7μm, and then drying at 90℃ for 90S to form a back coating layer 1 for standby use; then coating the stripping liquid on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 1μm, and then drying at 90℃ for 90S to form a stripping layer 3; then coating the curing liquid on the side of the stripping layer 3 away from the substrate 2 with a coating thickness of 0.5μm, and then drying at 90℃ for 90S to form a curing layer 4; coating the bonding liquid on the side of the curing layer 4 away from the substrate 2 with a coating thickness of 0.3μm, and then drying at 90℃ for 90S to form a bonding layer 5, thus obtaining an OC protective carbon tape.

[0084] Example 2: Preparation of OC protective carbon tape

[0085] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the stripping solution are different, and the rest of the steps are the same as those in embodiment 1. The specific step S1 is as follows:

[0086] S1: Preparation of liquid: Back coating liquid: the same as in Example 1; Stripping liquid: 15 parts of thermoplastic acrylic resin (MB-12; Bolier) and 5 parts of thermoplastic acrylic resin (MB-2; Bolier) are dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc (MICRO ACE P-3; Japan Talc), 1 part of dispersant (BYK180; Bi Ke), 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda) were mixed and dissolved to prepare a stripping solution for use; curing solution: 20 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) were dissolved in 38.2 parts of 2-butanone and 38.2 parts of toluene, and then 3 parts of isocyanate curing agent (TFD-90SB; Dornaide), 10 parts of ultraviolet absorber (Tinuvin 400; liquid; BASF) and 10 parts of ultraviolet absorber (Tinuvin1130; liquid; BASF) were added and mixed and dissolved to prepare a curing solution for use; bonding solution: 10 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) were dissolved in 43 parts of 2-butanone and 43 parts of toluene, and then 3 parts of talc powder (MICRO ACE P-3; Japan Talc) and 1 part of dispersant (LD-1010; Lida) were added and mixed and dissolved to prepare a bonding solution for use.

[0087] Example 3: Preparation of OC protective carbon tape

[0088] Compared with Example 1, the only difference between this embodiment and Example 1 is that the raw materials for preparing the solidifying liquid are different, and the rest of the steps are the same as those in Example 1. The specific step S1 is as follows:

[0089] S1: Preparation of liquid: Back coating liquid: the same as in Example 1; Stripping liquid: 15 parts of thermoplastic acrylic resin (MB-12; Bolier) and 5 parts of thermoplastic acrylic resin (MB-2; Bolier) are dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc (MICRO ACE P-3; Japan Talc), 1 part of dispersant (BYK180; Bi Ke), 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda) were mixed and dissolved to prepare a stripping solution for use; curing solution: 10 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) and 10 parts of hydroxy-modified acrylic resin (SGR-015A; Changhao) were dissolved in 38.2 parts of 2-butanone and 38.2 parts of toluene, and then 3 parts of isocyanate curing agent (TFD-90SB; Dornaide), 10 parts of ultraviolet absorber (Tinuvin 400; liquid; BASF) and 10 parts of ultraviolet absorber (Tinuvin 1130; liquid; BASF) were added and mixed and dissolved to prepare a curing solution for use; adhesive solution: 10 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) were dissolved in 43 parts of 2-butanone and 43 parts of toluene, and then 3 parts of talcum powder (MICRO ACE P-3; Japanese talc) and 1 part of dispersant (LD-1010; Lida) were mixed and dissolved together to prepare an adhesive solution for use.

[0090] Example 4: Preparation of OC protective carbon tape

[0091] Compared with Example 1, the only difference between this embodiment and Example 1 is that the raw materials for preparing the solidifying liquid are different, and the rest of the steps are the same as those in Example 1. The specific step S1 is as follows:

[0092] S1: Preparation of liquid: Back coating liquid: the same as in Example 1; Stripping liquid: 15 parts of thermoplastic acrylic resin (MB-12; Bolier) and 5 parts of thermoplastic acrylic resin (MB-2; Bolier) are dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc (MICRO ACE P-3; Japan Talc), 1 part of dispersant (BYK180; Bi Ke), 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda) were mixed and dissolved to prepare a stripping solution for use; curing solution: 10 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) and 10 parts of hydroxy-modified acrylic resin (SGR-015A; Changhao) were dissolved in 38.2 parts of 2-butanone and 38.2 parts of toluene, and then 3 parts of isocyanate curing agent (TFD-90SB; Dornaide), 8 parts of ultraviolet absorber (Tinuvin 400; liquid; BASF), 10 parts of ultraviolet absorber (Tinuvin 1130; liquid; BASF), and 2 parts of ultraviolet absorber (Tinuvin152 liquid; BASF) were mixed and dissolved to prepare a curing solution for use; adhesive solution: 10 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) were dissolved in 43 parts of 2-butanone and 43 parts of toluene, and then 3 parts of talcum powder (MICROACE P-3; Japanese talc) and 1 part of dispersant (LD-1010; Lida) were mixed and dissolved together to prepare an adhesive solution for use.

[0093] Example 5: Preparation of OC protective carbon tape

[0094] Compared with Example 1, the difference between this embodiment is that the resins for preparing the stripping liquid and the curing liquid are different, and the rest of the steps are the same as those in Example 1. The specific step S1 is as follows:

[0095] S1: Preparation of liquid: Back coating liquid: the same as in Example 1; Stripping liquid: 15 parts of thermoplastic acrylic resin (MB-12; Bolier) and 5 parts of thermoplastic acrylic resin (MB-2; Bolier) are dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc (MICRO ACE P-3; Japan Talc), 1 part of dispersant (BYK180; Bi Ke), 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda) were mixed and dissolved to prepare a stripping solution for use; curing solution: 10 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) and 10 parts of hydroxy-modified acrylic resin (SGR-015A; Changhao) were dissolved in 38.2 parts of 2-butanone and 38.2 parts of toluene, and then 3 parts of isocyanate curing agent (TFD-90SB; Dornaide), 8 parts of ultraviolet absorber (Tinuvin 400; liquid; BASF), 10 parts of ultraviolet absorber (Tinuvin 1130; liquid; BASF) and 2 parts of ultraviolet absorber (Tinuvin152 liquid; BASF) were mixed and dissolved together to prepare a curing liquid for use; bonding liquid: 5 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) and 5 parts of polyester modified acrylic resin (SGR-2600; Changhao) were dissolved in 43 parts of 2-butanone and 43 parts of toluene, and then 3 parts of talc powder (MICROACE P-3; Japan Talc) and 1 part of dispersant (LD-1010; Lida) were added and mixed and dissolved together to prepare a bonding liquid for use.

[0096] Comparative Example 1: Preparation of OC protective carbon tape

[0097] Compared with Example 1, the difference between this comparative example is that no stripping liquid, curing liquid and bonding liquid are prepared, and the remaining raw materials and steps are the same as those of Example 1. The specific step S1 is as follows:

[0098] S1: prepared solution: back coating solution: the same as in Example 1;

[0099] S2: Same as Example 1;

[0100] S3: coating: coating is performed by a gravure coater, firstly coating the back coating liquid on the corona-charged surface of the substrate 2, with a coating thickness of 0.7 μm, and then drying at 90° C. for 90 seconds to form a back coating layer 1, that is, to obtain an OC protective carbon tape.

[0101] Comparative Example 2: Preparation of OC protective carbon tape

[0102] Compared with Example 1, the difference between this comparative example is that no curing liquid and bonding liquid are prepared, and the remaining raw materials and steps are the same as those of Example 1. The specific step S1 is as follows:

[0103] S1: prepared solution: back coating solution: the same as in Example 1; stripping solution: the same as in Example 1;

[0104] S2: Same as Example 1;

[0105] S3: Coating: Coating is performed by a gravure coater, firstly coating the back coating liquid on the corona-charged surface of the substrate 2 with a coating thickness of 0.7 μm, and then drying at 90°C for 90S to form a back coating layer 1; then coating the stripping liquid on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 1 μm, and then drying at 90°C for 90S to form a stripping layer 3; that is, an OC protective carbon tape is obtained.

[0106] Comparative Example 3: Preparation of OC protective carbon tape

[0107] Compared with Example 1, the difference in this comparative example is that no stripping solution and bonding solution are prepared, and the remaining raw materials and steps are the same as those in Example 1. The specific steps are as follows:

[0108] S1: prepared liquid: back coating liquid: the same as in Example 1; curing liquid: the same as in Example 1;

[0109] S2: Same as Example 1;

[0110] S3: Coating: The coating is carried out by a gravure coater, firstly the back coating liquid is coated on the corona-charged surface of the substrate 2, the coating thickness is 0.7μm, and then it is dried at 90℃ for 90S to form a back coating layer 1; then the curing liquid is coated on the side of the substrate 2 away from the back coating layer 1, the coating thickness is 0.5μm, and then it is dried at 90℃ for 90S to form a curing layer 4; that is, the OC protective carbon tape is obtained.

[0111] Comparative Example 4: Preparation of OC protective carbon tape

[0112] Compared with Example 1, the difference in this comparative example is that no stripping liquid and curing liquid are prepared, and the remaining raw materials and steps are the same as those in Example 1. The specific steps are as follows:

[0113] S1: Preparation liquid: back coating liquid: the same as in Example 1; adhesive liquid: the same as in Example 1;

[0114] S2: Same as Example 1;

[0115] S3: Coating: Use a gravure coater to coat the back coating liquid on the corona-charged surface of the substrate 2 with a coating thickness of 0.7 μm, and then dry it at 90°C for 90S to form a back coating layer 1; coat the adhesive liquid on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 0.3 μm, and then dry it at 90°C for 90S to form a solidified layer 4; that is, an OC protective carbon tape is obtained.

[0116] Comparative Example 5: Preparation of OC protective carbon tape

[0117] Compared with Example 1, the difference between this comparative example is that no adhesive liquid and adhesive layer 5 are prepared, and the remaining raw materials and steps are the same as those of Example 1. The specific steps are as follows:

[0118] S1: prepared liquid: back coating liquid: the same as in Example 1; stripping liquid: the same as in Example 1; curing liquid: the same as in Example 1;

[0119] S2: Same as Example 1;

[0120] S3: Coating: Coating is performed by a gravure coater, firstly coating the back coating liquid on the corona-charged surface of the substrate 2 with a coating thickness of 0.7μm, and then drying at 90°C for 90S to form a back coating layer 1; then coating the stripping liquid on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 1μm, and drying at 90°C for 90S to form a stripping layer 3; finally, coating the curing liquid on the side of the stripping layer 3 away from the back coating layer 1 with a coating thickness of 0.5μm, and drying to form a curing layer 4, thereby obtaining an OC protective carbon tape.

[0121] Comparative Example 6: Preparation of OC protective carbon tape

[0122] Compared with Example 1, the difference between this comparative example is that no curing liquid and curing layer 4 are prepared, and the remaining raw materials and steps are the same as those of Example 1. The specific steps are as follows:

[0123] S1: Preparation liquid: back coating liquid: the same as in Example 1; stripping liquid: the same as in Example 1; bonding liquid: the same as in Example 1;

[0124] S2: Same as Example 1;

[0125] S3: Coating: Coating is performed by a gravure coater, firstly coating the back coating liquid on the corona-charged surface of the substrate 2 with a coating thickness of 0.7μm, and then drying at 90°C for 90S to form a back coating layer 1; coating the stripping liquid on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 1μm, and then drying at 90°C for 90S to form a stripping layer 3; finally, coating the adhesive liquid on the side of the stripping layer 3 away from the back coating layer 1 with a coating thickness of 0.3μm, and drying to form an adhesive layer 5, thereby obtaining an OC protective carbon tape.

[0126] Comparative Example 7: Preparation of OC protective carbon tape

[0127] Compared with Example 1, the difference between this comparative example and Example 1 is that the stripping solution and the stripping layer 3 are not prepared, and the remaining raw materials and steps are the same as those of Example 1. The specific steps are as follows:

[0128] S1: Preparation liquid: back coating liquid: the same as in Example 1; curing liquid: the same as in Example 1; bonding liquid: the same as in Example 1;

[0129] S2: Same as Example 1;

[0130] S3: Coating: The coating is carried out by a gravure coater, firstly the back coating liquid is coated on the corona-charged surface of the substrate 2 with a coating thickness of 0.7μm, and then it is dried at 90°C for 90S to form a back coating layer 1; the curing liquid is coated on the side of the substrate 2 away from the back coating layer 1 with a coating thickness of 0.5μm, and then it is dried at 90°C for 90S to form a curing layer 4; finally, the adhesive liquid is coated on the side of the stripping layer 3 away from the back coating layer 1 with a coating thickness of 0.3μm, and then it is dried to form an adhesive layer 5, thus obtaining an OC protective carbon tape.

[0131] Comparative Example 8: Preparation of OC protective carbon tape

[0132] The difference between this comparative example and Example 1 is that the type of ultraviolet absorber in the stripping solution is different, and the other raw materials and steps are the same as those in Example 1. The specific step S1 is as follows:

[0133] S1: Prepare liquid: back coating liquid: the same as in Example 1; stripping liquid: dissolve 20 parts of thermoplastic acrylic resin (BR-52; Mitsubishi) in 32.7 parts of toluene and 32.7 parts of 2-butanone, then add 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 2 parts of talc powder (MICROACE P-3; Japan Talc), 1 part of dispersant (BYK180; BYK), 20 parts of ultraviolet absorber (UV-477 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda), mix and dissolve together to make a stripping liquid for use; adhesive liquid: the same as in Example 1.

[0134] Comparative Example 9: Preparation of OC protective carbon tape

[0135] Compared with Example 1, the difference between this comparative example is that there is no talcum powder in the stripping solution, and the other raw materials and steps are the same as those in Example 1. The specific step S1 is as follows:

[0136] S1: Prepare liquid: Back coating liquid: the same as in Example 1; Stripping liquid: 20 parts of thermoplastic acrylic resin (BR-52; Mitsubishi) are dissolved in 32.7 parts of toluene and 32.7 parts of 2-butanone, and then 0.6 parts of release agent (erucic acid amide, melting point 79-83°C; Jiangxi Dongyuan), 20 parts of ultraviolet absorber (UV-477 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda) are added and mixed and dissolved to prepare a stripping liquid for use; Adhesive liquid: the same as in Example 1.

[0137] Comparative Example 10: Preparation of OC protective carbon tape

[0138] Compared with Example 1, the difference between this comparative example is that no release agent is added to the stripping solution, and the remaining raw materials and steps are the same as those of Example 1. The specific step S1 is as follows:

[0139] S1: Prepare liquid: back coating liquid: the same as in Example 1; stripping liquid: dissolve 20 parts of thermoplastic acrylic resin (BR-52; Mitsubishi) in 33 parts of toluene and 33 parts of 2-butanone, then add 20 parts of ultraviolet absorber (UV-460 solid; BASF), 10 parts of ultraviolet absorber (UV-120 solid; Milan Chemical), 0.4 parts of antioxidant (B-225; BASF), 0.6 parts of antistatic agent (Atmer 262; Hoda), 2 parts of talc (MICRO ACE P-3; Japan Talc), 1 part of dispersant (BYK180; BYK), mix and dissolve together to make a stripping liquid for use; curing liquid: the same as in Example 1; adhesive liquid: the same as in Example 1.

[0140] Comparative Example 11: Preparation of OC protective carbon tape

[0141] This comparative example is different from Example 1 in that the substrate 2 used is different, and the other raw materials and steps are the same as those of Example 1. The specific step S2 is as follows:

[0142] S2: A 4.5 μm PET film with a surface roughness Ra=0.04 nm was used as the substrate 2, and both surfaces of the substrate 2 were corona-charged.

[0143] Comparative Example 12: Preparation of OC protective carbon tape

[0144] Compared with Example 1, the difference between this comparative example is that the raw materials of the solidifying liquid are different, and the other raw materials and steps are the same as those of Example 1. The specific step S1 is as follows:

[0145] S1: Prepare liquid: back coating liquid: the same as in Example 1; stripping liquid: the same as in Example 1; curing liquid: dissolve 20 parts of polyhydroxy-modified vinyl chloride-acrylate resin (H15 / 40A; Wacker) in 39.5 parts of toluene and 39.5 parts of 2-butanone, then add 10 parts of ultraviolet absorber (Tinuvin 571 liquid; BASF), 10 parts of ultraviolet absorber (Tinuvin 292 liquid; BASF), and 3 parts of isocyanate curing agent (TFD-90SB; Dornaide) and mix and dissolve them together to make a curing liquid for use; adhesive liquid: the same as in Example 1.

[0146] Comparative Example 13: Preparation of OC protective carbon tape

[0147] Compared with Example 1, the difference between this comparative example is that the raw materials of the adhesive layer are different, and the other raw materials and steps are the same as those of Example 1. The specific step S1 is as follows:

[0148] S1: Prepare liquid: back coating liquid: the same as in Example 1; stripping liquid: the same as in Example 1; curing liquid: the same as in Example 1; bonding liquid: dissolve 10 parts of vinyl chloride-vinyl acetate resin (H11 / 59; Wacker) in 45 parts of 2-butanone and 45 parts of toluene to prepare a bonding liquid for use.

[0149] Comparative Example 14: Preparation of OC protective carbon tape

[0150] Compared with Example 1, the difference between this comparative example is that the particle size of the talc powder in the back coating layer is different, and the other raw materials and steps are the same as those in Example 1. The specific step S1 is as follows:

[0151] S1: Prepare liquid: Back coating liquid: dissolve 10 parts of polyvinyl butyral resin (S-LEC BH-6, Sekisui Chemical, Japan) in 60 parts of 2-butanone and 30 parts of toluene, then add 3 parts of isocyanate curing agent (TMHG-80B; Asahi Chemical, Japan), 0.6 parts of talcum powder with a D50 particle size of 6um and a D90 particle size of 13.5um (HY-TA05 D50; Haiyang Powder), 0.6 parts of phosphate ester (MOA-3PK-70; Jiangsu Haian Petrochemical Plant), and 0.5 parts of silicone oil (KF-965-100cs; Shin-Etsu Silicone), mix and dissolve together to prepare a back coating liquid for use; Stripping liquid: the same as in Example 1; Curing liquid: the same as in Example 1; Adhesive liquid: the same as in Example 1.

[0152] Test example: performance testing

[0153] The OC protective ribbons prepared in Examples 1-5 and Comparative Examples 1-14 were tested for printing using a DTP330 thermal sublimation soft label printer. The ribbons used were original ribbons. The print sample size was 6×6 inches. The printing speed was 6 m / min. The specific test items were as follows:

[0154] (1) Glossiness test and evaluation standards

[0155] The protective layers (peeling layer, curing layer, adhesive layer) of the OC protective carbon ribbons prepared in Examples 1-5 and Comparative Examples 1-14 were transferred to photo paper with black and white patterns using a DTP330 printer to obtain test samples, and then the 20° glossiness of a portion of the black area and a portion of the white area was measured using a Tri-Touch Screen Tri-Angle Gloss Meter NHG268, and the average value was read, and the glossiness was evaluated based on the evaluation criteria in Table 1 below. The evaluation results are shown in Table 3.

[0156] Table 1: Gloss evaluation criteria

[0157] A Glossiness evaluation result is 55 or above B The glossiness evaluation result is 35 or more and 55 or less C Glossiness evaluation result is 35 or less

[0158] (2) Alcohol friction resistance test and evaluation standards

[0159] The protective layer of the OC protective carbon ribbon prepared in Examples 1-5 and Comparative Examples 1-14 was transferred to a photo paper with a 16-step Cyan monochrome pattern using a DTP330 printer to obtain a test sample, and then the test sample was rubbed 1200 times with an alcohol friction tester DZ-204 and a WIP-1009D friction cloth at a weight of 500 g and a friction speed of 60 times / min. The color density of the test sample before and after friction was tested with an X-Rite i1-PRO3 colorimeter, the ratio of the color density after friction to that before friction was calculated, and the alcohol friction resistance was evaluated based on Table 2. The evaluation results are shown in Table 3.

[0160] Table 2: Color density evaluation criteria

[0161] A Ratio greater than or equal to 95% B Ratio greater than or equal to 80% less than 95% C Ratio greater than or equal to 60% less than 80% D Ratio less than 60%

[0162] (3) Weather resistance test

[0163] The OC protective carbon ribbon prepared in Examples 1-5 and Comparative Examples 1-14 was used to transfer the protective layer to photographic paper with yellow, magenta, and cyan densities of 0.5, 1.0, and the highest-order three-color monochrome pattern using a DTP330 printer. After obtaining the test sample, the color density before weathering was tested using an X-Rite i1-PRO3 colorimeter, and then aging was performed: a xenon lamp was used as the light source, which had a continuous spectrum at a wavelength between 300nm and 1200nm, and the illumination on the sample surface should be between 30klx and 100klx. A standard window glass filter was placed between the xenon light source and the sample. The blackboard temperature in the box was selected to be 40℃±3℃, the relative humidity was selected to be 50%±5%, the exposure period was 24h drying, and the artificial accelerated aging test time was 1200h. After the test was completed, the color density after weathering was tested using an X-Rite i1-PRO3 colorimeter, and the ratio of the color density after weathering to the color density before weathering was calculated. The calculation results are shown in Table 3.

[0164] Table 3

[0165]

[0166]

[0167] From Table 3, we can get:

[0168] (1) The glossiness and alcohol friction resistance evaluation results of the OC protective carbon ribbons of Examples 1-5 were both A, and the calculated weather resistance results were above 94.6%, with the highest being 98.4, which were better than the comprehensive performance of the OC protective carbon ribbons of Comparative Examples 1-14 during the thermal transfer process.

[0169] (2) Compared with the embodiments, the structures of the thermal transfer carbon ribbons of Comparative Examples 1-7 are different. The carbon ribbon structure of Comparative Example 1 only includes a substrate and a back coating layer, and has the worst performance. Comparative Example 2 has no curing layer or adhesive layer, and its weather resistance and alcohol friction resistance are reduced compared with Examples 1-5. Comparative Example 3 has no peeling layer or adhesive layer, and the test results show that all performances are poor, with a weather resistance of only 69.7%. Comparative Example 4 has no peeling layer or curing layer, and only the friction resistance is B, and the other performances are poor, with a weather resistance of only 15%. Comparative Example 5 has various performances comparable to those of the embodiments, but is not resistant to alcohol friction, which may be due to the lack of an adhesive layer. Comparative Example 6 lacks a curing layer, and the glossiness and alcohol friction resistance evaluation results are both A, but the weather resistance calculation result is poor, at 72.1%. Comparative Example 7 lacks a peeling layer, and only the alcohol friction resistance test result is better.

[0170] (3) The difference between Comparative Examples 8-14 and Example 1 lies in the different raw materials of each layer. The light stabilizer in the peeling layer of Comparative Example 8 uses a liquid ultraviolet absorber, the peeling layer of Comparative Example 9 does not add a solid lubricant, and the adhesive layer of Comparative Example 13 does not add an additive. The gloss test results of the three comparative examples are good, but all are not resistant to alcohol friction; no release agent is added to the peeling layer of Comparative Example 10; the surface roughness of the substrate used in Comparative Example 11 is relatively large, and the glossiness is average. The reason may be that the OC protective carbon ribbon of Comparative Example 10 has poor smoothness during high-speed printing, and the substrate of Comparative Example 11 has a relatively large surface roughness. The greater the surface roughness, the lower the glossiness. The curing layer in the OC protective carbon ribbon of Comparative Example 12 uses a non-reactive ultraviolet absorber. It can be seen that the setting of the curing layer in the OC protective carbon ribbon of the present invention and the non-reactive ultraviolet absorber added therein can greatly improve the weather resistance of the OC protective carbon ribbon and can meet the requirements of long-term reliable use.

[0171] In summary, the OC protective carbon tape provided by the present invention has a back coating layer 1 on one side of the substrate and an OC protective layer (including a peeling layer 3, a curing layer 4 and an adhesive layer 5) on the other side. The OC protective carbon tape obtained by the present invention can have good foil retention in high-speed printing, and can also take into account high weather resistance, high alcohol resistance and high gloss performance. It can be applied to different scenarios, which improves the use range and adaptability of thermal transfer carbon tape.

[0172] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An ultra-high weather-resistant OC protective carbon tape, characterized in that: The OC protective carbon tape comprises an adhesive layer, a curing layer, a peeling layer, a substrate, and a back coating layer arranged in sequence from top to bottom; The release layer comprises the following raw materials in parts by weight: 19-22 parts of a second resin, 0.5-0.7 parts of a release agent, 1.8-2.2 parts of a solid lubricant, 0.9-1.2 parts of a dispersant, 26-32 parts of a light stabilizer, 0.3-0.6 parts of an antioxidant, and 0.5-0.8 parts of an antistatic agent; The curing layer comprises the following raw materials in parts by weight: 18-22 parts of a third resin, 2-4 parts of an isocyanate curing agent, and 19-22 parts of a reactive light stabilizer; The adhesive layer comprises the following raw materials in parts by weight: 8-12 parts of a fourth resin, 2-4 parts of an auxiliary agent, and 0.8-1.1 parts of a dispersant.

2. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The back coating layer comprises the following raw materials in parts by weight: 9-11 parts of a first resin, 2-4 parts of an isocyanate curing agent, 0.5-1 parts of an inorganic filler, 0.5-0.9 parts of a release agent, and 0.3-0.5 parts of an organic silicone oil; The first resin is a thermoplastic resin; The isocyanate curing agent includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and aromatic isocyanate; The inorganic filler includes at least one of talc, kaolin, calcium carbonate, aluminum hydroxide, silicon dioxide, graphite, and boron nitride; The release agent in the back coating layer includes at least one of phosphate ester, metal soap, silicone oil, and surfactant.

3. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The second resin includes at least one of acrylonitrile-butadiene-styrene copolymer resin, polystyrene resin, polycarbonate resin, polymethyl methacrylate resin, polyacrylic acid resin, and thermoplastic acrylic resin; The release agent in the release layer is at least one of a solid release agent and a liquid release agent; The solid lubricant includes at least one of talcum powder, wax powder and metal soap; The dispersant in the peeling layer includes at least one of a cationic wetting dispersant, an anionic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, and a polymeric super dispersant; The light stabilizer in the release layer includes at least one of a light shielding agent, an ultraviolet absorber, a quencher, a free radical scavenger, and a hydroperoxide decomposer; The antioxidant includes at least one of a hindered phenol antioxidant, a phosphite antioxidant, a thio antioxidant, a composite antioxidant, and a hindered amine antioxidant; The antistatic agent includes at least one of sulfuric acid derivatives, phosphoric acid derivatives, amines, quaternary ammonium salts, imidazoles, and ethylene oxide derivatives.

4. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The third resin includes at least one of polyester resin, polyacrylate resin, styrene acrylate resin, polyurethane resin, polyethylene resin, polypropylene resin, polyolefin resin, polystyrene resin, polyvinyl chloride resin, polyvinyl butyral resin, amino resin, epoxy resin, hydroxyl-modified acrylic resin, polyhydroxyl-modified vinyl chloride-acrylate resin, polyester-modified acrylic resin, and acrylic-modified polyester resin; The isocyanate curing agent in the curing layer includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and aromatic isocyanate; The reactive light stabilizer includes at least one of a phenol compound ultraviolet absorber, a benzotriazole ultraviolet absorber, a benzophenone ultraviolet absorber, an oxalamide ultraviolet absorber, and a triazine ultraviolet absorber.

5. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The fourth resin includes at least one of cellulose-based resin, polyvinyl acetate resin, polyvinyl alcohol resin, polyurethane resin, polyamide resin, polyester resin, polyacrylic resin, polyolefin resin, polystyrene resin, styrene acrylate resin, vinyl chloride-acrylate resin, vinyl chloride-vinyl acetate resin, and vinyl chloride-vinyl isobutyl ether resin; The auxiliary agent includes at least one of inorganic particles and solid lubricants; The dispersant in the adhesive layer includes at least one of a cationic wetting dispersant, an anionic wetting dispersant, a nonionic wetting dispersant, an amphoteric wetting dispersant, and a polymeric super dispersant.

6. The ultra-high weather-resistant OC protective carbon tape according to claim 3, characterized in that: The solid release agent comprises at least one of polyethylene wax, palmitamide, ethylene bislauric acid amide, behenic acid amide, ethylene bisoleic acid amide, stearic acid amide, ethylene bisstearic acid amide, oleic acid amide, erucic acid amide, oleyl palmitamide, octadecyl stearic acid amide, octadecyl erucic acid amide, pentaerythritol tetrastearate, glyceryl trihydroxystearate, zinc stearate, zinc stearyl phosphate, calcium stearate, magnesium stearate, talc, and wax powder; The liquid release agent includes at least one of silicone oil, liquid paraffin, chlorinated paraffin, and n-butyl stearate.

7. The ultra-high weather-resistant OC protective carbon tape according to claim 5, characterized in that: The inorganic particles include at least one of silicon dioxide, aluminum oxide, titanium dioxide, molybdenum disulfide, calcium carbonate, and talc; when the auxiliary agent is the solid lubricant, the solid lubricant includes at least one of microcrystalline wax, carnauba wax, paraffin, low molecular weight polyethylene wax, wood wax, honey wax, spermaceti, wool wax, candelilla wax, vaseline, polyester wax, modified wax, and metal soap compounds.

8. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The substrate is a transparent flexible plastic film, including at least one of polypropylene, polyethylene naphthalate, polyethylene terephthalate, polyethylene, polyvinyl alcohol, and polymethyl methacrylate.

9. The ultra-high weather-resistant OC protective carbon tape according to claim 1, characterized in that: The thickness of the substrate is 4 μm-50 μm, and the surface roughness Ra is 0.02-0.1 nm; the thickness of the back coating is 0.4 μm-1.2 μm; the thickness of the peeling layer is 0.3-5 μm; the thickness of the curing layer is 0.3-5 μm; and the thickness of the bonding layer is 0.1-1 μm.

10. A method for preparing an ultra-high weather-resistant OC protective carbon tape according to any one of claims 1 to 9, characterized in that: The preparation method of the carbon ribbon is as follows: S1: Prepared liquid: Back coating liquid: Dissolve the first resin in a solvent, then add isocyanate curing agent, inorganic filler, and release agent to mix and dissolve to prepare back coating liquid for standby use; Stripping liquid: Dissolve the second resin in a solvent, then add release agent, solid lubricant, dispersant, light stabilizer, antioxidant, and antistatic agent to mix and dissolve to prepare stripping liquid for standby use; Curing liquid: Dissolve the third resin in a solvent, then add isocyanate curing agent and reactive light stabilizer to mix and dissolve to prepare curing liquid for standby use; Adhesive liquid: Dissolve the fourth resin in a solvent, then add auxiliary agent and dispersant to mix and dissolve to prepare adhesive liquid for standby use; S2: applying corona to one side of the substrate; S3: Coating: Apply the back coating liquid on the corona-charged surface of the substrate, and then dry it to form a back coating layer for standby use; then apply the stripping liquid on the side of the substrate away from the back coating layer, and then dry it to form a stripping layer; then apply the curing liquid on the side of the stripping layer away from the substrate, and then dry it to form a curing layer; apply the bonding liquid on the side of the curing layer away from the substrate, and then dry it to form a bonding layer, thereby obtaining an OC protective carbon tape.

Citation Information

Patent Citations

  • Protective resin thermal transfer ribbon for outdoor printed products and preparation method thereof

    CN115923367A

  • High-performance heat transfer printing resin thermal transfer ribbon, preparation method and application

    CN116512790A

  • Thermal transfer image receiving sheet

    JP2005238748A

  • Protective layer transfer sheet and intermediate transfer medium

    JP2014198435A

  • Non-flammable sheet

    JP2020163817A

Cited By

  • High-gloss thermal mounting protection thermal transfer ribbon with high weather resistance and assistant migration resistance

    CN120039056A